Direct Coupling of Thermo‐ and Photocatalysis for Conversion of CO2–H2O into Fuels. Issue 23 (14th November 2017) - Zhang, Li; Kong, Guoguo; Meng, Yaping; Tian, Jinshu; Zhang, Lijie; Wan, Shaolong; Lin, Jingdong; Wang, Yong
Abstract: Photocatalytic CO2 reduction into renewable hydrocarbon solar fuels is considered as a promising strategy to simultaneously address global energy and environmental issues. This study focused on the direct coupling of photocatalytic water splitting and thermocatalytic hydrogenation of CO2 in the conversion of CO2 –H2 O into fuels. Specifically, it was found that direct coupling of thermo‐ and photocatalysis over Au−Ru/TiO2 leads to activity 15 times higher ( T =358 K; ca. 99 % CH4 selectivity) in the conversion of CO2 –H2 O into fuels than that of photocatalytic water splitting. This is ascribed to the promoting effect of thermocatalytic hydrogenation of CO2 by hydrogen atoms generated in situ by photocatalytic water splitting. Abstract : The heat is on : Direct coupling of thermo‐ and photocatalysis over Au−Ru/TiO2 leads to 15 times higher activity ( T =358 K; ca. 99 % CH4 selectivity) in the conversion of CO2 –H2 O into fuels than purely photocatalytic water splitting, which is ascribed to the promoting effect of thermocatalytic hydrogenation of CO2 with hydrogen atoms generated in situ by photocatalytic water splitting.